2018
DOI: 10.1016/j.anr.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Alcohol Use on Antiretroviral Therapy Adherence in Koreans Living with HIV

Abstract: This study aimed to examine the impact of alcohol use on the antiretroviral therapy (ART) adherence of Koreans living with human immunodeficiency virus (HIV). Methods: A total of 144 HIV-infected Koreans older than the age of 19 years who had been receiving antiretroviral drugs for at least 3 months were surveyed. Alcohol use was identified as nonhazardous, binge, hazardous, and alcohol dependent as determined by the Alchol Use Disorder Identification Test-Korea (AUDIT-K). ART adherence was defined according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Our finding that those with suboptimal adherence in the previous year were more likely to experience moderate-to-severe depressive symptoms and report moderate-to-high risk substance use adds to the substantial body of evidence from this region linking mental health issues, substance use and poorer adherence across different adult PLHIV populations [ 20 , 32 , 39 43 ]. Our finding that mean CD4 cell count and viral load < 1000 copies/mL were not risk factors for moderate-to-high risk substance use or moderate-to-severe depressive symptoms, adds to the insubstantial and conflicting regional evidence of associations between mental health or substance use and HIV clinical or treatment outcomes.…”
Section: Discussionmentioning
confidence: 62%
“…Our finding that those with suboptimal adherence in the previous year were more likely to experience moderate-to-severe depressive symptoms and report moderate-to-high risk substance use adds to the substantial body of evidence from this region linking mental health issues, substance use and poorer adherence across different adult PLHIV populations [ 20 , 32 , 39 43 ]. Our finding that mean CD4 cell count and viral load < 1000 copies/mL were not risk factors for moderate-to-high risk substance use or moderate-to-severe depressive symptoms, adds to the insubstantial and conflicting regional evidence of associations between mental health or substance use and HIV clinical or treatment outcomes.…”
Section: Discussionmentioning
confidence: 62%
“…These factors were comparable to those found in previous studies. Alcohol use [46][47][48][49][50] may reduce adherence because alcohol consumption lowers the concentration and reasoning capacity of the consumer, causing them to miss doses, especially on drinking days. 46 Stigma was another reason, as identified in previous studies; [51][52][53] this because it causes a diminished desire to take medication, self-rejection, and depression, leading to poor adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with alcohol use disorder are unable to control their alcohol use which can result in unhealthy consequences [17].Alcohol use disorders are common among PLWHA [18]. Recent studies conducted in different countries showed that the prevalence of alcohol use disorder among PLWHA ranges from 14.0% to 38.4% [18][19][20][21][22][23][24][25][26], which was 3-times higher than the general population (5.8%−11.1%) [17] [27]. A recent meta-analysis that analyzed a total of 25 studies with more than 25,000 participants from 2010 to 2019 showed that the pooled estimated prevalence of alcohol use disorder among PLWHA was 29.8% [18].…”
Section: Incidence Of Alcohol Use Among Plwhamentioning
confidence: 99%
“…Recent clinical studies conducted from different countries also showed the impact of alcohol use on adherence to ART [23,26] [30,31] [30]. For example, a study in Korea showed the increase in alcohol consumption was related to a decrease in adherence to ART [26]. The ratio of patients with less than 95% ART adherence for binge drinkers, hazardous drinkers, and alcohol dependents were 4.65%, 8.05%, and 27.67%, respectively.…”
Section: Effects Of Alcohol On Art Adherencementioning
confidence: 99%